Ethics in International Marketing - Isayeva, Aygul (International Journal of Economic Practices and Theories, 2014)
The importance of ethics in international marketing, but not only, has managed across time to maintain itself as a well disputed and investigated subject. This study sets for itself to create a general view of the issue by relying on previous examinations of the matter conducted by researchers all over the world and adding some complementary practical information through a detailed analyzed case study. The aim of this article is to illustrate the constantly increasing importance of an ethically conscientious marketing and to draw the attention towards acting in a responsible manner.